Cumulative Signaling Through NOD-2 and TLR-4 Eliminates the Mycobacterium Tuberculosis Concealed Inside the Mesenchymal Stem Cells - Aqdas, Mohammad; Singh, Sanpreet; Amir, Mohammed; Maurya, Sudeep Kumar; Pahari, Susanta; Agrewala, Javed Naim (Frontiers in Cellular and Infection Microbiology, 2021)
For a long time, tuberculosis (TB) has been inflicting mankind with the highest morbidity and mortality. Although the current treatment is extremely potent, a few bacilli can still hide inside the host mesenchymal stem cells (MSC). The functional capabilities of MSCs are known to be modulated by TLRs, NOD-2, and RIG-1 signaling. Therefore, we hypothesize that modulating the MSC activity through TLR-4 and NOD-2 can be an attractive immunotherapeutic strategy to eliminate the Mtb hiding inside these cells. In our current study, we observed that MSC stimulated through TLR-4 and NOD-2 (N2.T4) i) activated MSC and augmented the secretion of pro-inflammatory cytokines; ii) co-localized Mtb in the lysosomes; iii) induced autophagy; iv) enhanced NF-κB activity via p38 MAPK signaling pathway; and v) significantly reduced the intracellular survival of Mtb in the MSC. Overall, the results suggest that the triggering through N2.T4 can be a future method of immunotherapy to eliminate the Mtb concealed inside the MSC.